Water Quality Modeling That Works - Lung, Wu-Seng. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a practical guidance for environmental engineers and scientists charged with assessing the cause-and-effect of pollutants in receiving water systems. Instead of blindly running models, which is a practice seen too often in today's field that can result in results with uncertainty, modelers must first understand the physical insights of the specific water systems in order to properly calibrate the parameters of the models. This book reinforces the critical importance of properly understanding the physical attributes of water systems by drawing on the author's extensive experience in modeling with strong data support. This is also what sets this book apart from the volumes currently available in the water quality modeling field - nearly all other books in the field are categorized as textbooks, and unlike this book, offer few practical examples or exercises to follow. Environmental engineers and scientists engaged in quantifying the water quality impacts of pollutants to specific water systems will find this book valuable in their day-to-day practices. This book is a necessary volume for water quality engineers and scientists to consult for the regulatory planning and management of water systems.
1. Challenges of Modeling for Water Quality Management -- 2. Data Analysis to Understand the Modeled System -- 3. River BOD/DO Modeling with New Twists -- 4. Eutrophication Modeling: Algal Blooms, Nutrients, and Dissolved Oxygen -- 5. Modeling Analysis for pH -- 6. Modeling Pathogens in Natural Waters and Sediments -- 7. Toxics and Emerging Chemicals -- 8. Mixing Zone Analysis.
Keywords: Water; Hydrology; Environmental chemistry; Environmental management; Environment; Refuse and refuse disposal; Environmental engineering; Biotechnology; Bioremediation; Water; Environmental Chemistry; Environmental Management; Environmental Sciences; Waste Management/Waste Technology; Environmental Engineering/Biotechnology.